Henry Simon tells some tales - Thomas, Gerald (1973)
Henry Simon conte «Old John Snipe/The old guesser » [Vieux John Snipe/le vieux devineur], qu’il a appris de Frank Woods. Il parle de Cyril Robin, conteur et chanteur. Il conte le conte de St-Pierre qui se montre plus malin que le diable. Ensuite il parle des veillées. -- Henry Simon tells the tale "Old John Snipe/The old guesser", which he learned from Frank Woods. He talks about Cyril Robin, singer and storyteller. He tells the tale of St. Peter outwitting the Devil. Then he talks about “veillées” [times].